Perancangan dan Pembelajaran Awal Sistem Informasi Posyandu Terbarukan bagi Warga Desa Kuripan Kecamatan Karangawen Kabupaten Demak - Siti Kholifah; Paulus Hartanto; Rini Rubhiyanti (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2019)
This research is in the background behind the making of posyandu activity reports every month which experience problems in data processing. Technology that is currently developing can be used to help process posyandu data. Then the posyandu information system for toddler is designed to help in the monthly posyandu data processing and learning process product. The purpose and this research is to design, posyandu information systems for toddler that are valid, practical, and effective to be used in the process of posyandu activities and learning process. The method used in this study is the waterfall method with the requirements analysis, system design, implementation, integration and system testing, and operation and maintenance stages. System design includes use cases, flowcharts, context diagrams, data flow diagrams, entity relationship diagrams, design tables and input process output designs. Then implemented into PHP programming language by using the MYSQL database. The results showed that expert validation with an average percentage by media experts was 84% and material experts were 85.95% so it can be concluded that the information system is very valid. Cadre response was 87.1 so it can be concluded that the information system is very good. Practical test results with an average percentage of 85.24% which means very good so that it can get practical information. The results of the effectiveness test using the IKP formula were obtained at 85% so it can be concluded that the information system is very effective to use.